Generation of human iPSC line from a patient with laterality defects and associated congenital heart anomalies carrying a DAND5 missense alteration - Cristo, Fernando (2017)
We would like to thank the patient and their guardians for their generous donation of the urine sample used in this study. We also would like to thank Ana Jardimfor technical support in karyotype analysis. This work was supported by Fundacao para a Ciencia e a Tecnologia (PTDC/BIM-MED/3363/2014). iNOVA4Health - UID/Multi/04462/2013, a program financially supported by Fundacao para a Ciencia e Tecnologia/Ministerio da Educacao e Ciencia, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement is acknowledged. Publisher